Inocencia - Fitzgerald, Penelope; Adón, Pilar, 1971-; Dooley, Terence, 1950- (Madrid : Impedimenta, 2014)
Beautiful Chiara is the last of the Ridolfi, a Florentine family of long lineage and eccentric habits. She is smitten with Salvatore, a brilliant but penniless doctor a rational man who wants nothing to do with romance. This is the story of how these two -- with the best intentions, the kindest of instincts, and the most meddlesome of friends -- make each other wonderfully miserable.
Online resource; title from ePub title page (Digitalia, viewed February 18, 2018)
Keywords: Young women -- Fiction; Florence (Italy) -- Fiction; Upper class -- Fiction; Physicians -- Fiction; Italy -- Fiction; Romance fiction; Electronic books